The effect of cubic potentials on discrete breathers in a mixed Klein-Gordon/Fermi-Pasta-Ulam chain - 周倩 吕彬彬 田强 (Chinese physics B, 2010)
Nonlinearity has a crucial impact on the symmetry properties of dynamical systems. This paper studies a one-dimensional mixed Klein-Gordon/Fermi Pasta-Ulam diatomic chain using the expanded rotating plane-wave approximation and numerical calculations to determine the effect of cubic potentials on the symmetry properties of discrete breathers in this system. The results will be very useful to researchers in the field of numerical calculations on discrete breathers.